Metal surface structuring with spatiotemporally focused femtosecond laser pulses. (20th December 2017) - Tan, Yuanxin; Chu, Wei; Lin, Jintian; Fang, Zhiwei; Liao, Yang; Cheng, Ya
Abstract: Femtosecond laser micromachining provides high precision and less thermal diffusion in surface structuring as a result of the ultrashort duration and ultrahigh peak intensity of the femtosecond laser pulses. To increase the throughput of surface patterning, the focal spot size can be expanded with loose focusing, which, however, could lead to nonlinear self-focusing of the pulses when the pulses propagate in air. We solve the problem by use of spatiotemporally focused femtosecond laser pulses for ablation of metal surfaces, which gives rise to improved surface quality as compared with that obtained with the conventional focusing scheme.